Communicating knowledge publishing in the 21st century - Feather, John; Gale Group (Munchen K.G. Saur, 2003)
"This book provides an introduction to publishing practices in the context of the information society, concentrating on its structure and operation."--GVRL description.
Electronic reproduction.
Keywords: Publishers and publishing; Publishers and publishing -- Technological innovations; Electronic publishing; Electronic books